2021
DOI: 10.7759/cureus.16207
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Viral Infection Among Beta-Thalassemia Patients: A Study From the Centre for Excellence in Thalassemia and Other Blood Disorders

Abstract: BackgroundHepatitis C virus (HCV) is a single-stranded RNA virus, which is frequently transmitted through blood transfusions, contact with infected blood or blood products, and vertical transmission. Injectable drug abusers and transplant recipients are predisposed to HCV infection. It causes acute hepatitis, which may progress to chronic hepatitis, and in severe untreated cases, patients may develop cirrhosis and hepatocellular carcinoma (HCC). Since there is no vaccine available against HCV infection, preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The major end points of the NCT03877809 clinical trial were not aimed to explore changes in the functionality of memory T cells of Sirolimus‐treated patients. 39 However, the possible effect of Sirolimus in β‐Thalassemia is intriguing, as recent reports have highlighted a high mortality rate in β‐Thalassemia patients affected by infectious bacterial and viral diseases, 41 , 42 , 43 , 44 , 45 , 46 probably due to co‐existing immune deficiencies. 47 , 48 , 49 Immune dysfunctions characterizing thalassemia patients include changes in lymphocyte subsets, such as the accumulation of suppressor T cells and the reduced proliferative capacity and numbers of T helper cells, as well as the defective activity of natural killer (NK) cells.…”
Section: Introductionmentioning
confidence: 99%
“…The major end points of the NCT03877809 clinical trial were not aimed to explore changes in the functionality of memory T cells of Sirolimus‐treated patients. 39 However, the possible effect of Sirolimus in β‐Thalassemia is intriguing, as recent reports have highlighted a high mortality rate in β‐Thalassemia patients affected by infectious bacterial and viral diseases, 41 , 42 , 43 , 44 , 45 , 46 probably due to co‐existing immune deficiencies. 47 , 48 , 49 Immune dysfunctions characterizing thalassemia patients include changes in lymphocyte subsets, such as the accumulation of suppressor T cells and the reduced proliferative capacity and numbers of T helper cells, as well as the defective activity of natural killer (NK) cells.…”
Section: Introductionmentioning
confidence: 99%
“…In blood donors' seroprevalence for hepatitis B, C and HIV were 2.35%, 3.26% and 0.17% 14 . Although all patients of thalassemia major receiving blood transfusion are prone to acquire these infectious diseases but our study showed that the patients who receive transfusion frequently and in whom it started earlier are more liable to become positive than those in whom interval between transfusion is relatively increased to maintain haemoglobin 5 .…”
Section: Discussionmentioning
confidence: 56%
“…It's the hemoglobin H variety who is severely anemic and needs transfusion for whole life 3 . Blood transfusion in these patients is like two faces of a coin whose one side saves lives and keep the functions going on but on the other side it has devastating effects if goes unchecked 2,5 . One of the hazardous effects of transfusion is transmission of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…9.4% of the cases in our study had HCV serology that was positive. While Mirzaei et al [17] reported a lesser percentage (3.4%), Al-Khabori et al [11], Elalfy et al [12], and Kandi et al [18] recorded greater percentages (38%, 82%, and 28%, respectively) of HCV antibody positive individuals. According to our research, having a positive HCV serology was associated with the severity of liver fibrosis (p value 0.05).…”
Section: Discussionmentioning
confidence: 99%